PENGARUH PEMBERIAN ORAL HYGIENE DENGAN POVIDONE IODINE 1% TERHADAP PENCEGAHAN KEJADIAN VENTILATOR ASSOCIATED PNEUMONIA (VAP) DI RUANG ICU RSUD dr. HARYOTO LUMAJANG - Ni Komang Tri Pramesuari; Ruris Haristiani; Adi Yunanto Adi Yunanto; Yudho Tri Handoko (Institut Kesehatan Hermina, 2024)
Ventilator Associated Pneumonia (VAP) is a lung parenchymal infection that occurs in patients after using mechanical ventilation for 48-72 hours. Patients with ventilator associated pneumonia (VAP) will show new or progressive infiltrates on chest x-ray, experience systemic infections such as fever and changes in white blood cell count, changes in sputum characteristics, and indicate detection of the causative agent in patients with VAP. Preventive measures to prevent the occurrence of VAP in ICU is oral hygiene. Oral hygiene is an oral care procedure to clean the mouth, teeth and gums using 1% povidone iodine. This study aims to evaluate the effect of administering oral hygiene with 1% Povidone Iodine in preventing Ventilator Associated Pneumonia (VAP) in patient users. Mechanical Ventilator in the ICU at Dr. Haryoto Lumajang Hospital. The research method used is a case study method. The research instrument used in this research is Standard Operating Procedures (SOP). Modified Clinical Pulmonary Infection Score (MCPIS) observation sheet. The results showed that the MCPIS score from day 1 to day 8 was ?5 so that the patient was declared not diagnosed with VAP after being given oral hygiene intervention with povidone iodine 1% with a frequency of 2 times a day for 8 days. It is hoped that this research will be an effort to prevent the occurrence of VAP in patients using mechanical ventilators and be able to reduce patient mortality rates.